2008
DOI: 10.1111/j.1399-3046.2008.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating non‐adherence to immunosuppressant medications in pediatric liver transplant recipients

Abstract: Non-adherence with recommended immunosuppressant medications is common post-pediatric liver transplant and is the most important reason for organ rejection in long-term survivors. However, there is currently no validated, standard method to measure adherence, with a well-defined threshold, making it extremely difficult to evaluate interventions to improve adherence. Previous studies have suggested that the degree of fluctuation of medication blood levels over time can provide an idea about how regularly the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 17 publications
3
93
0
2
Order By: Relevance
“…In liver transplantation, the effect of non-adherence on graft outcomes has been well studied in pediatric and adolescent transplant recipients [7][8][9][10][11]. Among adults, various international studies have attempted to measure non-adherence to IS therapy using self-reported non-adherence [12] and electronic medication monitoring [13], with the majority of patients found to be adherent to IS therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In liver transplantation, the effect of non-adherence on graft outcomes has been well studied in pediatric and adolescent transplant recipients [7][8][9][10][11]. Among adults, various international studies have attempted to measure non-adherence to IS therapy using self-reported non-adherence [12] and electronic medication monitoring [13], with the majority of patients found to be adherent to IS therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The calcineurin inhibitors, such as cyclosporine and tacrolimus (TAC), are the cornerstone of any pediatric immunosuppression protocol. Variable TAC levels are a primary indicator of medication non-adherence, which is common with adolescent and young adult transplant patients [14]. The 10-year kidney allograft survival for adolescents ages 12–18 years and young adults 19–24 is the lowest among all age groups, averaging 40.1% for deceased donors and 52.9% for living donor recipient [5].…”
Section: Introductionmentioning
confidence: 99%
“…Related questions of considerable importance are to what extent a patient needs to adhere to the prescribed treatment to obtain clinical benefits, and at what point nonadherence is likely to result in a clinically meaningful difference in response. This so-called "adherence threshold" is an important yet understudied area of investigation [17]. Yet, since a large number of youth with ADHD start and restart medication, sometimes repeatedly, over the course of several years [18], understanding the adherence threshold will illuminate the extent to which this pattern of behavior is seen as problematic.…”
Section: Defining and Understanding Adherencementioning
confidence: 99%